A photoresistor material and preparation method thereof
By injecting transition metal ions and rare earth metal ions into sulfur quantum dots and annealing treatment, metal sulfide quantum dots are formed, which solves the problem of insufficient photoelectric conversion efficiency and crystallization performance of photoresistor materials in the prior art, and achieves more efficient photoelectric conversion and lower resistance values.
Patent Information
- Application Number
- CN202510004169.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-02
AI Technical Summary
There are few researches on photoresistor materials in the prior art, especially in the study of photoresistors using sulfur quantum dots, there are challenges in improving photoelectric conversion efficiency and improving crystallization performance.
By injecting transition metal ions (such as Cd ions) and rare earth metal ions (such as La ions) into sulfur quantum dots and annealing in an argon environment, metal sulfide quantum dots are formed, thereby improving the photoelectric conversion efficiency and crystallization performance of photoresistor materials.
It achieves a greater photocurrent under the same light conditions, improves the photoelectric conversion efficiency, improves the crystallization performance of photoresistor materials, reduces the resistance value, and broadens the application field of sulfur quantum dots.
Smart Images

Figure CN119384085B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of semiconductor materials, in particular to a photoresistor material and a preparation method thereof. Background Art
[0002] Photoresistors are photoconductive devices made of semiconductor materials. Due to their advantages such as small size, large operating current, fast reaction speed and wide spectral response range, photoresistors are widely used in photoelectric control, automatic control and communication.
[0003] Photoresistors are extremely sensitive to changes in light. In a dark environment without light, they are in a high-resistance state, and the current flowing through the circuit is very small. Under light conditions, the resistance decreases rapidly and the current flowing through increases. As a new type of "zero-dimensional" luminescent nanomaterial, sulfur quantum dots have received widespread attention from researchers since they were first reported in 2014. Sulfur quantum dots have shown great application potential in many fields due to their excellent photoluminescent properties, good biocompatibility, and rich precursor sources. However, most related research focuses on cell imaging, antibacterial treatment, light-emitting device manufacturing, and photocatalysis, and there is little research on photoresistors. Summary of the invention
[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a photoresistor material and a preparation method thereof.
[0005] The technical solutions adopted are as follows:
[0006] The present invention provides a method for preparing a photoresistor material:
[0007] Transition metal ions and rare earth metal ions are injected into the sulfur quantum dots successively;
[0008] The implantation dose of transition metal ions and rare earth metal ions is 1×10 15 cm -2 -10×10 15 cm -2 ;
[0009] The implantation energy of transition metal ions and rare earth metal ions is 100keV-200keV;
[0010] The transition metal ion is a Cd ion;
[0011] The rare earth metal ion is La ion;
[0012] After ion implantation, annealing is required in an argon environment at a temperature of 250-350°C and a time of 10-60 minutes.
[0013] Furthermore, the preparation method of the sulfur quantum dots is as follows:
[0014] Dissolve sublimated sulfur powder, sodium hydroxide and surfactant in deionized water, first react in a water bath at 50-80°C under ultrasonic treatment for 1-10 hours, transfer the resulting reaction solution to a hydrothermal reactor, seal it, heat it to 140-180°C and continue to react for 1-10 hours, return to room temperature after the reaction is completed, dialyze the reaction solution with a dialysis bag for 36-72 hours, collect the dialyzed product and freeze-dry it at low temperature.
[0015] Furthermore, the mass ratio of the sublimated sulfur powder, sodium hydroxide and surfactant is 1-10:1-10:1-10.
[0016] Furthermore, the surfactant is any one of polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600.
[0017] Furthermore, the molecular weight cut-off of the dialysis bag is 100Da-1000Da.
[0018] The present invention also provides a photoresistor material, which is prepared by the above-mentioned method for preparing the photoresistor material.
[0019] Beneficial effects of the present invention:
[0020] The present invention provides a photoresistor material. The present invention uses transition metal ions to implant sulfur quantum dots to form corresponding metal sulfide quantum dots, so that the photoresistor material has a photoresistor effect. The implantation of rare earth metal ions can not only promote the growth of the metal sulfide quantum dots, but also reduce the optical band gap thereof, improve the absorption of light by the photosensitive material, generate a larger photocurrent under the same illumination conditions, and improve the photoelectric conversion efficiency. Annealing can effectively improve the crystallization performance of the photoresistor material, improve its absorbance in the visible light region, and generate more electron-hole pairs under the same illumination, so as to have a lower resistance. The present invention broadens the application field of the sulfur quantum dots and provides a new path for the preparation of the photoresistor material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The structure diagram of the photoresistor in Example 1, the icon numbers represent:
[0022] 1-Si (100) substrate, 2-Cd ion / La ion implanted sulfur quantum dot film, 3-aluminum electrode;
[0023] Figure 2 This is the voltage waveform during inkjet printing in Example 1. DETAILED DESCRIPTION
[0024] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0025] Embodiment 1:
[0026] A photoresistor, comprising a Si (100) substrate, a Cd ion / La ion implanted sulfur quantum dot film and an aluminum electrode, specifically Figure 1 ;
[0027] The preparation method of the above-mentioned photoresistor is as follows:
[0028] Sublimed sulfur powder, sodium hydroxide and polyethylene glycol 400 with a mass ratio of 4:4:2 were dissolved in deionized water with a solid-liquid mass ratio of 1:10. The obtained mixed solution was first reacted in a water bath at 60°C under ultrasonic treatment for 5 hours, and then the reaction solution was transferred to a hydrothermal reactor and sealed and heated to 150°C for further reaction for 8 hours. After the reaction was completed, the room temperature was restored, and the reaction solution was dialyzed with a 1000Da dialysis bag for 72 hours. During this period, deionized water was replaced every 12 hours. The dialyzed product was collected and freeze-dried at -50°C for 24 hours to obtain sulfur quantum dots;
[0029] Sulfur quantum dots were added to a solvent composed of cyclohexylbenzene and octadecene in a mass ratio of 10:1, and ultrasonic treatment was performed for 30 min to obtain a quantum dot solution with a concentration of 50 mg / ml. The quantum dot solution was loaded into the ink cartridge of a JetLab II printer, and a sulfur quantum dot film was printed on the surface of a Si (100) substrate using an inkjet printer. During printing, a 5V voltage was first slowly applied to push the droplets out of the nozzle, and then a 5V reverse voltage was quickly applied to reduce the droplet tailing. The voltage waveform parameters are shown in Figure 2 , the number of printed drops was set to 2 drops per pixel pit, the droplet spacing was 20 μm, and it took 15 min to print the entire Si (100) substrate. The entire printing process was carried out in air. After printing, the Si (100) substrate was placed on a hot plate at 80 °C for annealing for 15 min to remove residual solvent;
[0030] Then, 10×10 15 cm -2 The Cd ions with a dose of 150 keV were injected into the sulfur quantum dot film. During the injection process, the Cd ions were incident vertically along the surface of the sulfur quantum dot film. 15 cm -2The La ions with a dose of 150 keV were injected into the sulfur quantum dot film. During the injection process, the La ions were incident vertically along the surface of the sulfur quantum dot film. After the ion injection, the film was annealed in an argon environment at a temperature of 300°C and a time of 30 minutes.
[0031] Finally, aluminum electrodes were evaporated on the sulfur quantum dot film using a mask, with an electrode spacing of 200 μm and an electrode thickness of 100 nm.
[0032] The light and dark resistance-voltage characteristics of the photoresistor prepared in this embodiment are obtained by using a Keithley 2400 digital source meter and a 10LUX light source illumination. The light resistance value of the photoresistor is about 0.52MΩ, the dark resistance value is about 2.95MΩ, and both remain constant within the voltage range of 1-10V, indicating that the prepared photoresistor material has typical photoresistance characteristics.
[0033] Embodiment 2:
[0034] A photoresistor comprises a Si (100) substrate, a Cd ion / La ion implanted sulfur quantum dot film and an aluminum electrode;
[0035] The preparation method of the above-mentioned photoresistor is as follows:
[0036] Sublimed sulfur powder, sodium hydroxide and polyethylene glycol 400 with a mass ratio of 4:4:2 were dissolved in deionized water with a solid-liquid mass ratio of 1:10. The obtained mixed solution was first reacted in a water bath at 60°C under ultrasonic treatment for 5 hours, and then the reaction solution was transferred to a hydrothermal reactor and sealed and heated to 150°C for further reaction for 8 hours. After the reaction was completed, the room temperature was restored, and the reaction solution was dialyzed with a 1000Da dialysis bag for 72 hours. During this period, deionized water was replaced every 12 hours. The dialyzed product was collected and freeze-dried at -50°C for 24 hours to obtain sulfur quantum dots;
[0037] Sulfur quantum dots were added to a solvent composed of cyclohexylbenzene and octadecene in a mass ratio of 10:1, and ultrasonically treated for 30 minutes to obtain a quantum dot solution with a concentration of 50 mg / ml. The quantum dot solution was loaded into an ink cartridge of a JetLab II printer, and a sulfur quantum dot film was printed on the surface of a Si (100) substrate using an inkjet printer. During printing, a 5V voltage was first slowly applied to push the droplets out of the nozzle, and then a 5V reverse voltage was quickly applied to reduce the droplet tailing. The voltage waveform parameters were the same as those in Example 1. The number of printed drops was set to 2 drops per pixel pit, and the droplet spacing was 20 μm. It took 15 minutes to print the entire Si (100) substrate. The entire printing process was performed in air. After printing, the Si (100) substrate was placed on a hot plate at 80° C. for annealing for 15 minutes to remove residual solvent.
[0038] Then, 10×1015 cm -2 The Cd ions with a dose of 150 keV were injected into the sulfur quantum dot film. During the injection process, the Cd ions were incident vertically along the surface of the sulfur quantum dot film. 15 cm -2 The La ions with a dose of 150 keV were injected into the sulfur quantum dot film. During the injection process, the La ions were incident vertically along the surface of the sulfur quantum dot film. After the ion injection, the film was annealed in an argon environment at a temperature of 250°C and a time of 30 min.
[0039] Finally, aluminum electrodes were evaporated on the sulfur quantum dot film using a mask, with an electrode spacing of 200 μm and an electrode thickness of 100 nm.
[0040] The light and dark resistance-voltage characteristics of the photoresistor prepared in this embodiment are obtained by a Keithley 2400 digital source meter and a 450W xenon lamp under an illumination of 450Lx. The light resistance value of the photoresistor is about 0.66MΩ, the dark resistance value is about 2.96MΩ, and both remain constant within the voltage range of 1-10V, indicating that the prepared photoresistor material has typical photoresistance characteristics.
[0041] Embodiment 3:
[0042] A photoresistor comprises a Si (100) substrate, a Cd ion / La ion implanted sulfur quantum dot film and an aluminum electrode;
[0043] The preparation method of the above-mentioned photoresistor is as follows:
[0044] Sublimed sulfur powder, sodium hydroxide and polyethylene glycol 400 with a mass ratio of 4:4:2 were dissolved in deionized water with a solid-liquid mass ratio of 1:10. The obtained mixed solution was first reacted in a water bath at 60°C under ultrasonic treatment for 5 hours, and then the reaction solution was transferred to a hydrothermal reactor and sealed and heated to 150°C for further reaction for 8 hours. After the reaction was completed, the room temperature was restored, and the reaction solution was dialyzed with a 1000Da dialysis bag for 72 hours. During this period, deionized water was replaced every 12 hours. The dialyzed product was collected and freeze-dried at -50°C for 24 hours to obtain sulfur quantum dots;
[0045] Sulfur quantum dots were added to a solvent composed of cyclohexylbenzene and octadecene in a mass ratio of 10:1, and ultrasonically treated for 30 minutes to obtain a quantum dot solution with a concentration of 50 mg / ml. The quantum dot solution was loaded into an ink cartridge of a JetLab II printer, and a sulfur quantum dot film was printed on the surface of a Si (100) substrate using an inkjet printer. During printing, a 5V voltage was first slowly applied to push the droplets out of the nozzle, and then a 5V reverse voltage was quickly applied to reduce the droplet tailing. The voltage waveform parameters were the same as those in Example 1. The number of printed drops was set to 2 drops per pixel pit, and the droplet spacing was 20 μm. It took 15 minutes to print the entire Si (100) substrate. The entire printing process was performed in air. After printing, the Si (100) substrate was placed on a hot plate at 80° C. for annealing for 15 minutes to remove residual solvent.
[0046] Then, 10×10 15 cm -2 The Cd ions with a dose of 150 keV were injected into the sulfur quantum dot film. During the injection process, the Cd ions were incident vertically along the surface of the sulfur quantum dot film. 15 cm -2 The La ions with a dose of 150 keV were injected into the sulfur quantum dot film. During the injection process, the La ions were incident vertically along the surface of the sulfur quantum dot film. After the ion injection, the film was annealed in an argon environment at a temperature of 350°C and a time of 30 min.
[0047] Finally, aluminum electrodes were evaporated on the sulfur quantum dot film using a mask, with an electrode spacing of 200 μm and an electrode thickness of 100 nm.
[0048] The light and dark resistance-voltage characteristics of the photoresistor prepared in this embodiment are obtained by a Keithley 2400 digital source meter and a 450W xenon lamp under an illumination of 450Lx. The light resistance value of the photoresistor is about 0.61MΩ, the dark resistance value is about 2.96MΩ, and both remain constant within the voltage range of 1-10V, indicating that the prepared photoresistor material has typical photoresistance characteristics.
[0049] Comparative Example 1:
[0050] It is basically the same as Example 1, except that La ion implantation is not performed.
[0051] A photoresistor comprises a Si (100) substrate, a Cd ion-implanted sulfur quantum dot film and an aluminum electrode;
[0052] The preparation method of the above-mentioned photoresistor is as follows:
[0053] Sublimed sulfur powder, sodium hydroxide and polyethylene glycol 400 with a mass ratio of 4:4:2 were dissolved in deionized water with a solid-liquid mass ratio of 1:10. The obtained mixed solution was first reacted in a water bath at 60°C under ultrasonic treatment for 5 hours, and then the reaction solution was transferred to a hydrothermal reactor and sealed and heated to 150°C for further reaction for 8 hours. After the reaction was completed, the room temperature was restored, and the reaction solution was dialyzed with a 1000Da dialysis bag for 72 hours. During this period, deionized water was replaced every 12 hours. The dialyzed product was collected and freeze-dried at -50°C for 24 hours to obtain sulfur quantum dots;
[0054] Sulfur quantum dots were added to a solvent composed of cyclohexylbenzene and octadecene in a mass ratio of 10:1, and ultrasonically treated for 30 minutes to obtain a quantum dot solution with a concentration of 50 mg / ml. The quantum dot solution was loaded into an ink cartridge of a JetLab II printer, and a sulfur quantum dot film was printed on the surface of a Si (100) substrate using an inkjet printer. During printing, a 5V voltage was first slowly applied to push the droplets out of the nozzle, and then a 5V reverse voltage was quickly applied to reduce the droplet tailing. The voltage waveform parameters were the same as those in Example 1. The number of printed drops was set to 2 drops per pixel pit, and the droplet spacing was 20 μm. It took 15 minutes to print the entire Si (100) substrate. The entire printing process was performed in air. After printing, the Si (100) substrate was placed on a hot plate at 80° C. for annealing for 15 minutes to remove residual solvent.
[0055] Then, 10×10 15 cm -2 The Cd ions with a dose of 150 keV were injected into the sulfur quantum dot film. During the injection process, the Cd ions were incident vertically along the surface of the sulfur quantum dot film. After the ion injection, the film was annealed in an argon environment at a temperature of 300°C and a time of 30 minutes.
[0056] Finally, aluminum electrodes were evaporated on the sulfur quantum dot film using a mask, with an electrode spacing of 200 μm and an electrode thickness of 100 nm.
[0057] The light and dark resistance-voltage characteristics of the photoresistor prepared in this comparative example were obtained by using a Keithley 2400 digital source meter and a 10LUX light source illumination. The light resistance value of the photoresistor was approximately 1.47MΩ, the dark resistance value was approximately 2.93MΩ, and both remained constant within the voltage range of 1-10V, indicating that the prepared photoresistor material had typical photoresistance characteristics.
[0058] Comparative Example 2:
[0059] It is basically the same as Example 1, except that no annealing treatment is performed.
[0060] A photoresistor comprises a Si (100) substrate, a Cd ion / La ion implanted sulfur quantum dot film and an aluminum electrode;
[0061] The preparation method of the above-mentioned photoresistor is as follows:
[0062] Sublimed sulfur powder, sodium hydroxide and polyethylene glycol 400 with a mass ratio of 4:4:2 were dissolved in deionized water with a solid-liquid mass ratio of 1:10. The obtained mixed solution was first reacted in a water bath at 60°C under ultrasonic treatment for 5 hours, and then the reaction solution was transferred to a hydrothermal reactor and sealed and heated to 150°C for further reaction for 8 hours. After the reaction was completed, the room temperature was restored, and the reaction solution was dialyzed with a 1000Da dialysis bag for 72 hours. During this period, deionized water was replaced every 12 hours. The dialyzed product was collected and freeze-dried at -50°C for 24 hours to obtain sulfur quantum dots;
[0063] Sulfur quantum dots were added to a solvent composed of cyclohexylbenzene and octadecene in a mass ratio of 10:1, and ultrasonically treated for 30 minutes to obtain a quantum dot solution with a concentration of 50 mg / ml. The quantum dot solution was loaded into an ink cartridge of a JetLab II printer, and a sulfur quantum dot film was printed on the surface of a Si (100) substrate using an inkjet printer. During printing, a 5V voltage was first slowly applied to push the droplets out of the nozzle, and then a 5V reverse voltage was quickly applied to reduce the droplet tailing. The voltage waveform parameters were the same as those in Example 1. The number of printed drops was set to 2 drops per pixel pit, and the droplet spacing was 20 μm. It took 15 minutes to print the entire Si (100) substrate. The entire printing process was performed in air. After printing, the Si (100) substrate was placed on a hot plate at 80° C. for annealing for 15 minutes to remove residual solvent.
[0064] Then, 10×10 15 cm -2 The Cd ions with a dose of 150 keV were injected into the sulfur quantum dot film. During the injection process, the Cd ions were incident vertically along the surface of the sulfur quantum dot film. 15 cm -2 The dose of La ions is injected into the sulfur quantum dot film at an energy of 150 keV. During the injection process, the La ions are incident vertically along the surface of the sulfur quantum dot film.
[0065] Finally, aluminum electrodes were evaporated on the sulfur quantum dot film using a mask, with an electrode spacing of 200 μm and an electrode thickness of 100 nm.
[0066] The light and dark resistance-voltage characteristics of the photoresistor prepared in this comparative example were obtained by using a Keithley 2400 digital source meter and a 10LUX light source illumination. The light resistance value of the photoresistor was approximately 1.65MΩ, the dark resistance value was approximately 2.96MΩ, and both remained constant within the voltage range of 1-10V, indicating that the prepared photoresistor material had typical photoresistance characteristics.
[0067] By comparing the data of Examples 1-3, it can be seen that different annealing temperatures have a certain influence on the photoresistance value of the photoresistor, and the photoresistance value is the smallest when the annealing temperature is 300°C.
[0068] By comparing the data of Example 1 with Comparative Examples 1-2, it can be seen that both La ion implantation and annealing treatment can greatly reduce the photoresistance value.
[0069] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a photoresistor material, characterized in that: The sulfur quantum dots are injected with transition metal ions and rare earth metal ions in sequence; The implantation dose of transition metal ions and rare earth metal ions is 1×10 15 cm -2 -10×10 15 cm -2 ; The implantation energy of transition metal ions and rare earth metal ions is 100keV-200keV; The transition metal ion is a Cd ion; The rare earth metal ion is La ion; After ion implantation, annealing is required in an argon environment at a temperature of 250-350°C and a time of 10-60 minutes.
2. The method for preparing a photoresistor material according to claim 1, characterized in that: The preparation method of the sulfur quantum dots is as follows: Dissolve sublimated sulfur powder, sodium hydroxide and surfactant in deionized water, first react in a water bath at 50-80°C under ultrasonic treatment for 1-10 hours, transfer the resulting reaction solution to a hydrothermal reactor, seal it, heat it to 140-180°C and continue to react for 1-10 hours, return to room temperature after the reaction is completed, dialyze the reaction solution with a dialysis bag for 36-72 hours, collect the dialyzed product and freeze-dry it at low temperature.
3. The method for preparing a photoresistor material according to claim 2, characterized in that: The mass ratio of the sublimated sulfur powder, sodium hydroxide and surfactant is 1-10:1-10:1-10.
4. The method for preparing a photoresistor material according to claim 2, characterized in that: The surfactant is any one of polyethylene glycol 200, polyethylene glycol 400 and polyethylene glycol 600.
5. The method for preparing a photoresistor material according to claim 2, characterized in that: The molecular weight cut-off of the dialysis bag is 100Da-1000Da.
6. A photoresistor material, characterized in that: The photoresistor material is prepared by the preparation method of any one of claims 1 to 5.
Citation Information
Patent Citations
Light sensitive material for preparing high-sensitivity ultraviolet visible light responding light dependent resistor
CN106847953A
Light-sensitive material for preparing low-cost ultraviolet visible light responding light dependent resistor
CN106847994A